Serious game to simulate and raise awareness about accessibility problems in the urban context - Almeida, Eduardo Antonio Comerão Stecca; Feitosa, Juliana da Costa; Brega, José Remo Ferreira (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
The lack of accessibility in urban areas reinforces the need to develop solutions that contribute to understanding the difficulties faced by people in wheelchairs. Many existing solutions present concepts related to the topic in a non-intuitive way, without worrying about user involvement and immersion. This work is a serious game developed to simulate and expose these main challenges through the use of concepts of immersion, simulation, and player experience. Aimed at teenagers and young adults who have access to a mobile device, the objective is to improve the user’s understanding by subjecting them to a three-dimensional environment close to reality. WheelChair Simulator was developed to be used as a complementary tool in various use cases, such as schools and environments that encourage this type of theme, in a practical and accessible way. Finally, it is expected that the game will be evaluated in the future by potential users.